User satisfaction of the grade 7 to 4th year high school students of the School Library of Philippine National School for the Blind - Vizcarra, Jamie Anne T. (School of Library and Information Studies, University of the Philippines Diliman, 2014)
School libraries contribute in developing the minds of children by complementing the curriculum of the school and instilling in children the love for reading. People with disabilities are one of the undeserved groups in the library. They also have the right to access needed information. A library should serve the whole school population. It should satisfy its users and encourage non-users to utilize what the library has to offer.